Pengembangan Alat Pelontar Bola Sepak Untuk Melatih Keterampilan Penjaga Gawang - Saputra , Randyka Cahya Saputra; Putro , Danang Endarto; Astuti , Ridha Kurniasih (Universitas Mercu Buana Yogyakarta, 2025)
The aim of this research is to develop a soccer ball throwing device that can be used to train goalkeeper skills in the sport of soccer. The research employs a development method (Research and Development/R&D), consisting of several stages: (1) Potential and Problems, (2) Information Collection, (3) Product Design, (4) Product Validation, (5) Design Improvement, (6) Product Testing, (7) Product Revision, (8) Product Testing, (9) Product Revision, and (10) Final Product. The instruments used in this study include observation, interviews, questionnaires, and documentation. Product validation was conducted by material and media experts. Data analysis was performed using the Likert scale.The results of the research showed: (1) material expert validation data scored 46 (92%), categorized as